Comparative accuracy of magnetic resonance morphometry and sonography in assessment of post-cesarean uterine scar - Satpathy, Gayatri; Kumar, Ishan; Matah, Manjari; Verma, Ashish (Indian Journal of Radiology and Imaging, 2018)
Objective: To compare the diagnostic accuracy of magnetic resonance imaging (MRI) with that of ultrasonography (USG) for the measurement of lower segment cesarean scar during trial of labor after cesarean (TOLAC). Materials and Methods: This was a prospective case-control observational study conducted with a cohort of 30 participants being considered for TOLAC but eventually proceeding to lower segment cesarean section (LSCS) at a university-based teaching institute over a period of 2 years. Measurement of scar thicknesses were done by MRI and USG preoperatively and validated by surgical findings. Comparison of diagnostic accuracy as well as the cut-off values (to differentiate a normal scar from an abnormal scar) was done between the two modalities. Results: Insignificant systematic error between the measurements obtained by the two modalities was noted by a Bland–Altmann analysis. The diagnostic accuracy of USG for differentiating a normal from an abnormal uterine scar was 96.7% while that of MRI was at a slightly lower level of 90%. A strong level of agreement between the two modalities was observed. Conclusion: MRI offers no advantage in diagnostic accuracy for the measurement of LSCS scar thickness during consideration of TOLAC. Advances in Knowledge: Measurement of uterine scar by MRI has a good correlation with that done on USG in the setting of post-cesarean pregnancy. The results hold good both for normal (grades 1 and 2) and abnormal (grades 3) scars. MRI, however, does not offer any added advantage over sonographic scar thickness measurement for the differentiation of a normal (grades 1 and 2) from an abnormal (grade 3) scar.
Keywords: Lower segment caesarian section; magnetic resonance imaging; scar thickness; uterine scar; vaginal birth after cesarean